Magnetic resonant imaging features of acute traumatic cervical spinal cord injury: Its correlation with american spinal injury association impairment scale and prediction of neurological improvement using a low tesla magnetic resonant imaging in a resource-constrained environment - Alfin, Jeneral; Yusuf, Ayodeji; Mahmud, Raji; Shilong, Danaan; Bot, Gyang; Yiltok, Simon (Nigerian journal of orthopaedics and trauma, 2021)
Context: Traumatic spinal cord injury (TSCI) is a devastating disease, hence the need to identify clinical and radiological injury features that can predict neurological improvement. Aims: This study aims to identify magnetic resonant imaging (MRI) features in cervical TSCI that correlates with neurological status at admission, and also predict early neurological improvement. Settings and Design: This was a prospective cohort study. Subjects and Methods: Admission MRI features of 47 patients with cervical TSCI and their neurological assessments at admission and 3 months post-injury were reviewed prospectively over a period of 18 months. Correlational and regression analyses were done using SPSS® version 25 software. P < 0.05 was used as the level of significance. Results: Spinal cord oedema and cord contusion (78.0%) constitute the majority of injury patterns seen on MRI. There was a significant association between spinal cord contusion and cord oedema on MRI and incomplete TSCI. Likewise, spinal cord haemorrhage, compression and transection were associated with complete TSCI. Maximum canal compromise (MCC), maximum spinal cord compression (MSCC) and length of cord lesion significantly correlate with American Spinal Injury Association Impairment Scale at admission (P = 0.033, P = 0.015 and P < 0.001, respectively). Increasing values of these variables were found to be independent predictors of complete TSCI. However, length of cord lesion was the only independent predictor of neurological improvement, 3 months post-injury (P = 0.025). Conclusions: Spinal cord haemorrhage, compression, transection and higher values of MCC, MSCC and increased length of cord lesion were predictive of complete TSCI. However, the length of spinal cord lesion was a better predictor of early neurological improvement.